Kidney Organoids as Disease Models: Strengths, Weaknesses and Perspectives - Romero-Guevara, Ricardo; Ioannides, Adonis; Xinaris, Christodoulos (Frontiers in Physiology, 2020)
Chronic kidney disease (CKD) is a major global health problem, as it affects 10% of the global population and kills millions of patients every year. It is therefore of the utmost importance to develop models that can help us to understand the pathogenesis of CKD and improve our therapeutic strategies. The discovery of human induced pluripotent stem cells (hiPSCs) and, more recently, the development of methods for the generation of 3D organoids, have opened the way for modelling human kidney development and disease in vitro, and testing new drugs directly on human tissue. In this review we will discuss the most recent advances in the field of kidney organoids for modelling disease, as well as the prospective applications of these models for drug screening. We will also emphasize the impact of CRISPR/cas9 genome engineering on the field, point out the current limitations of the existing organoid technologies, and discuss a set of technical developments that may help to overcome limitations and facilitate the incorporation of these exciting tools into basic biomedical research.